Pengaruh Penerapan Good Corporate Governance dan Solvabilitas Terhadap Peringkat Obligasi Pada Industri Perbankan - Saromah , Tati; Woestho, Choiroel (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
This research was conducted to determine how the effect of the implementation of good corporate governance and solvency on bond ratings. This research is conducted because there is still little research on the prediction of bond ratings in Indonesia. This is due to the limited data on bonds and investors' understanding of bonds. The purpose of this study are to determine the partial and simultaneous effect of good corporate governance and solvency on bond ratings in the banking industry in 2007-2015. The research analysis method used in this research is Multiple Discriminant Analysis (MDA) which consists of classical assumption tests, multiple linear regression tests, and hypothesis testing. This type of research is quantitative using secondary data and the sampling technique used is purposive sampling. The results in this study are partially Good Corporate Governance (X1) has a significant positive effect on bond ratings (Y), and Solvency (X2) has no effect on bond ratings (Y), as well as simultaneously Good Corporate Governance (X1) and Solvency (X2). ) has a significant effect on bond ratings (Y).